2011
DOI: 10.1103/physrevlett.106.127003
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field-Tuned Quantum Phase Transition in the Insulating Regime of Ultrathin Amorphous Bi Films

Abstract: A surprisingly strong variation of resistance with perpendicular magnetic field, and a peak in the resistance vs. field, R(B) has been found in insulating films of a sequence of homogeneous, quench-condensed films of amorphous Bi undergoing a thicknesstuned superconductor-insulator transition. Isotherms of magnetoresistance, rather than resistance, vs. field were found to cross at a well-defined magnetic field higher than the field corresponding to the peak in R(B). For all values of B, R(T ) was found to obey… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
15
1
Order By: Relevance
“…Since the ρ xx maxima predicted by the standard HLN model (indicated by the blue curves) occur at a substantially lower B than those observed in experiments, ρ xx for B < B p cannot be solely described by spin-orbit coupling in the normal state and thus must be related to superconductivity. Such results are reminiscent of the intriguing influence of disorder on superconductivity27282930313233. In a disordered superconductor subject to a strong perpendicular magnetic field, insulating behavior can occur.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Since the ρ xx maxima predicted by the standard HLN model (indicated by the blue curves) occur at a substantially lower B than those observed in experiments, ρ xx for B < B p cannot be solely described by spin-orbit coupling in the normal state and thus must be related to superconductivity. Such results are reminiscent of the intriguing influence of disorder on superconductivity27282930313233. In a disordered superconductor subject to a strong perpendicular magnetic field, insulating behavior can occur.…”
Section: Resultsmentioning
confidence: 92%
“…29), and Bi (ref. 31). Strong disorder, which is believed to be detrimental to superconductivity, plays a crucial role in maintaining superconductivity in such systems.…”
Section: Resultsmentioning
confidence: 99%
“…We will only focus on those models expected to be in the same universality class as our model (z ¼ 1); a more complete history can be found in Ref. [49] and the references therein.…”
Section: Appendix C: Universal Conductivity and Critical Exponentsmentioning
confidence: 99%
“…It has been found that even such samples exhibit a nonmonotonic magnetoresistance with a prominent peak resulting in a high-B phenomenology of the transport that is similar to their superconducting counterparts. 7,[21][22][23][24] We will refer to these samples as insulators, distinguishing them from the more standard superconductors.…”
mentioning
confidence: 99%